Karakterisasi Produk Metil Ester Hasil Reaksi Interesterifikasi RPO (Refined Palm Oil) dengan Katalis Kalium Hidroksida - Elvianto Dwi Daryono (Jurnal Serambi Engineering, 2026)
The transesterification process in biodiesel production is less effective because there is a separation stage of the glycerol byproduct. The interesterification process is more effective because the triacetin byproduct does not need to be separated and functions as an antioxidant in biodiesel. Stirring speed and catalyst are very important factors for a reaction to occur. Stirring will increase the frequency factor of collisions between reacting particles while the catalyst at a certain amount will accelerate the reaction. The study aims to determine the effect of stirring speed and KOH catalyst concentration on the interesterification reaction of RPO (Refined Palm Oil). The weight of RPO is 250 g, the mole ratio of oil: methyl acetate is 1: 6, stirring speed (200 - 60 rpm), KOH catalyst (0.25 - 0.75%), reaction temperature is 60℃ and reaction time is 1 hour. RPO, methyl acetate and KOH are put into a three-neck flask and the reaction is according to the operating conditions. After the reaction is complete, washing with hot water and CH3COOH is added to neutralize the KOH catalyst. The reaction products are separated with a separating funnel and the resulting phase is washed with distilled water until the pH is neutral. After that, it was distilled and the residue was the result of the reaction which was then analyzed for concentration with GC and its physical properties. The optimum conditions were obtained in the RPO interesterification reaction at a stirring speed of 300 rpm with 0.75% KOH catalyst which produced FAME with a concentration of 33,818 mg/L and an acid value of 0.438 mg KOH/g according to SNI 7182:2015.